Dispute processes : ADR and primary forms of decision-making - Palmer, Michael J. E., 1944-; Roberts, Simon (Simon A.) (Cambridge, UK ; New York, NY : Cambridge University Press, 2020)
"The International Journal of Law in Context is the companion journal to the Law in Context book series and provides a forum for interdisciplinary legal studies and offers intellectual space for ground-breaking critical research. It publishes contextual work about law and its relationship with other disciplines including but not limited to science, literature, humanities, philosophy, sociology, psychology, ethics, history and geography. More information about the journal and how to submit an article can be found at http://journals.cambridge.org/ijc"--
Introduction -- Cultures of decision-making : precursors to the emergence of ADR -- The debates around civil justice and the movement towards procedural innovation -- Disputes and dispute processes -- Development of disputes, avoidance, self help -- Negotiations -- Mediation -- Umpiring : courts and tribunals -- Umpiring : arbitration -- Hybrid forms and processual experimentation -- The ombuds and its diffusion : from public to privat -- ODR and its diffusion : from private to public -- Institutionalization of ADR -- Reflections.
Includes bibliographical references and index.
Hye Trade International
Keywords: Dispute resolution (Law); Law -- History